Unpacking the effects of personality traits on algorithmic awareness: The mediating role of previous knowledge and moderating role of internet use - Fang, Wei; Jin, Jianbin (Frontiers in Psychology, 2022)
Algorithms are increasingly being utilized by online platforms to tailor the selection and presentation of online content. Users’ awareness of algorithmic curation influences their ability to properly calibrate their reception of online content and interact with it accordingly. However, there has been a lack of research exploring the factors that contribute to users’ algorithmic awareness, especially in the roles of personality traits. In this study, we explore the influence of Big Five personality traits on internet users’ algorithmic awareness of online content and examine how this relationship is mediated by previous knowledge relating to algorithms within the context of China. We adapted the 13-item Algorithmic Media Content Awareness Scale (AMCA-scale) to survey users’ algorithmic awareness of online content in four dimensions. Our data were collected using a survey of a random sample of internet users in China (n = 885). The results of our study suggest that the Big Five traits have no direct effect on users’ algorithmic awareness and that previous knowledge mediates the relationship between three dimensions of the Big Five traits (extraversion, agreeableness, and open-mindedness) and algorithmic awareness.